Integration of Religion and Science in Nidhal Guessoum’s Thought: An Epistemological Analysis and Its Implications for Islamic Education - Toedien, Faisal Amir; Dewi, Eva (AJIS: Academic Journal of Islamic Studies, 2025)
This study aims to analyze the concept of the integration of religion and science from Nidhal Guessoum’s perspective, with a particular focus on its epistemological dimension and its relevance to the development of contemporary Islamic education. The study is motivated by the limited number of works that examine in depth the epistemological aspects of Guessoum’s integrative paradigm, while discourse on the integration of knowledge in the Muslim world has largely been dominated by normative approaches such as the Islamization of knowledge. This research employs a library research method with source triangulation and a descriptive-analytical approach through an examination of Guessoum’s major works and relevant scholarly literature. The findings indicate that the paradigm of knowledge integration he proposes is grounded in three main principles: the non-contradiction between revelation and science, layered interpretation, and theistic falsification. This approach rejects rigid models of i‘jaz al-Qur’an and the Islamization of knowledge, while emphasizing a rational dialogue between religion and science. This study contributes theoretically to the strengthening of Islamic epistemology and offers practical implications for the development of Islamic education that is scientific, contextual, and open to scientific advancement.